ИЗГОТОВЛЕНИЕ ТРАФАРЕТНЫХ ПЕЧАТНЫХ ФОРМ (ТПФ) ПРИ ПИГМЕНТНОЙ ПЕЧАТИ - Джураева Шахнозахон Гайратовна (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Abstract: The article provides recommendations on the preparation, application and reuse of stencil molds for pigment printing.